About research in entrepreneurship - Rosero Sarasty, Oscar M.; Molina, Sandra L. (Informes Psicológicos, 2008)
The frameworks of this article refer to the identification of certain trends and theoretical orientations regarding the topic of entrepreneurship. The topic is presented considering three elements that impact it: the entrepreneurial individual, entrepreneurial development and entrepreneurial learning. In the entrepreneurial individual, entrepreneurship is approached from the singularity of the subject, explaining the motivations, characteristics and traits that entrepreneurial individuals have. Entrepreneurial development is approached from a perspective where both the external aspects of the subject and the internal or personal ones are factors that determine the viability of the venture; The presence of Universities to train entrepreneurs and the importance of these as a factor in the country’s development is highlighted. As a strategy for entrepreneurial learning, cognitive conceptions referred to both knowledge and other processes such as decision-making, innovation and creativity are emphasized. These processes must be articulated with a model of social cognition where teamwork contributes to entrepreneurship.